2016
DOI: 10.1051/meca/2016033
|View full text |Cite
|
Sign up to set email alerts
|

Conformal heating/cooling channels design in rapid heat cycle molding process

Abstract: A three-dimensional study of the thermal regulation system of Rapid Heat Cycle Molding process producing complex-shaped automotive part was undertaken. This numerical study aims at improving the design of thermal control system so as to improve the quality of the molded part and the process productivity. The thermal responses in mold and cavity are predicted by the commercial Finite Volume Analysis software Fluent 6.3.26 in cyclic transient regime. It was shown that a regular regime is established from the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…1a), a first design of heating/cooling channels is proposed as shown in Figure 1b. The adopted arrangement of heating/ cooling channels has recently been studied and proved to be efficient for the RHCM process (Kria et al [15]). In addition to horizontal channels, circumventing the automotive part shape, the thermal control system includes vertical channels to access to convex zones in cavity/core plates in order to enhance heat transfer in these regions during the RHCM process.…”
Section: Effect Of Heating/cooling Channels Design On Rhcm Process Efmentioning
confidence: 99%
See 3 more Smart Citations
“…1a), a first design of heating/cooling channels is proposed as shown in Figure 1b. The adopted arrangement of heating/ cooling channels has recently been studied and proved to be efficient for the RHCM process (Kria et al [15]). In addition to horizontal channels, circumventing the automotive part shape, the thermal control system includes vertical channels to access to convex zones in cavity/core plates in order to enhance heat transfer in these regions during the RHCM process.…”
Section: Effect Of Heating/cooling Channels Design On Rhcm Process Efmentioning
confidence: 99%
“…They [13] have demonstrated an improvement of 27.3% in the heating efficiency when changing the original design by the optimal configuration. More recently, Hammami et al [14] and Kria et al [15] have demonstrated, through 3D numerical thermal regulation studies of RHCM molds, the necessity of carrying out simulations of several heating/cooling cycles until reaching the regular regime since they have found a strong difference between the first cycle and the regular one. They [14][15] have shown that since the second heating/cooling cycle the regular regime is reached.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the fact that not only the surface but the whole mold is heated to increase the surface temperature. To solve this disadvantage of increased cooling time, new techniques are developed, such as conformal cooling and algorithms that provide better distribution of cooling channels or optimized heating procedure [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%